Production of erythroid-potentiating activity by a human T-lymphoblast cell line. - Golde, D W (1980)
We derived a human T-lymphoblast cell line (Mo) that constitutively elaborates certain lymphokines. The Mo cells produce a colony-stimulating factor necessary for the growth of human granulocyte-monocyte precursors in vitro as well as an erythroid-potentiating activity (EPA) that enhances the proliferation of human erythroid progenitors in vitro. In the presence of serum, the EPA in Mo-conditioned medium stimulated the growth of small and large erythroid colonies almost 2-fold. EPA was also produced in serum-free medium, and, when assayed in serum-free cultures of human erythroid progenitors, it stimulated colony growth about 3-fold. The EPA produced by the Mo cell line did not stimulate normal murine erythroid progenitors (CFU-E) or Friend erythroleukemia cell growth in vitro. EPA was inactivated by protease treatment but was remarkably heat stable, with most of the activity recovered after boiling for 15 min. Preliminary biochemical characterization suggests that EPA is an acidic glycoprotein with molecular weight approximately 45,000. EPA is clearly separable from colony-stimulating factor on the basis of heat stability and gel-filtration chromatography. The present observations provide strong support for the concept that activated T cells produce humoral factors important in the regulation of erythropoiesis. The availability of a cell line producing human EPA should facilitate the characterization of the protein and permit definitive studies of its biologic effects.